Zoobenthos and sediments time series in southern Königshafen, Sylt, Germany, in 2007 - Werner Armonies (PANGAEA, 2022)
In parallel to an ongoing time series in the subtidal of List Reede, 12 fixed sites were sampled in the adjoining intertidal area between September 2003 and June 2012. Analyses comprised abundances and species composition of macrozoobenthos (sieve size 1 mm) and granulometric sediment composition. This dataset contains the results from six sampling dates in 2007.
In: Armonies, W (2022): Zoobenthos and sediments time series in southern Königshafen, Sylt, Germany, 2003 to 2012 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.947293